2018
DOI: 10.1007/s13197-018-3487-1
|View full text |Cite
|
Sign up to set email alerts
|

Milling and thermal treatment induced changes on phenolic components and antioxidant activities of pigmented rice flours

Abstract: Processing methods involved in value addition to pigmented broken rice, a milling by-product may affect the nutraceutical qualities. Hence the effect of pulverisation and toasting on nutraceutical content in brown rice flours of red and black rice varieties were studied. Plate milling reduced soluble, bound and total polyphenols in red, but increased in black; increased insoluble polyphenols and oryzanol, and reduced anthocyanin in both varieties; antioxidant activity is reduced in red, but increased in black.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 25 publications
2
16
1
Order By: Relevance
“…In comparison with the previous studies, the effects of thermal treatments on TPC values of soluble- and insoluble-bound phenolic fractions in natural products were contradictory, which may be due to the different conditions for thermal treatments and different samples used for study. For example, Sapna et al found that thermal treatment significantly increased TPC in the soluble-conjugated fraction but decreased the TPC value in soluble-free and insoluble-bound fractions of red rice flour, which was in line with the results of tomato seeds after baking for 15 and 60 min in the present study. Kim and colleagues found that the content of free phenolics generally increased after heat processing in rice hull, whereas the content of bound phenolics decreased compared with that of the raw rice hull .…”
Section: Resultssupporting
confidence: 92%
“…In comparison with the previous studies, the effects of thermal treatments on TPC values of soluble- and insoluble-bound phenolic fractions in natural products were contradictory, which may be due to the different conditions for thermal treatments and different samples used for study. For example, Sapna et al found that thermal treatment significantly increased TPC in the soluble-conjugated fraction but decreased the TPC value in soluble-free and insoluble-bound fractions of red rice flour, which was in line with the results of tomato seeds after baking for 15 and 60 min in the present study. Kim and colleagues found that the content of free phenolics generally increased after heat processing in rice hull, whereas the content of bound phenolics decreased compared with that of the raw rice hull .…”
Section: Resultssupporting
confidence: 92%
“…Grain phenolic compounds were eliminated during rice milling and flour preparation, as indicated by a low TPC in CMRF. In comparison to unmilled rice, Sapna et al [ 37 ] found that the TPC of milled rice retained roughly 73–89% of the overall TPC.…”
Section: Discussionmentioning
confidence: 99%
“…Rice can be differentiated based on its colours such as brown, white (polished brown rice), red, purple or black, and more importantly based on its geographical origin. White rice is the most widely consumed rice, however, pigmented rice such as black rice has higher overall health-beneficial components [6,7] (Table 1). Geographical origin or place of production influences the characteristics or quality of food, and ultimately the purchasing decision of consumers [8].…”
Section: Introductionmentioning
confidence: 99%